No side difference between achilles tendon characteristics in female Division One collegiate gymnasts post exercise: Preliminary study - Hartog, P.; Hinkle, L. J.; Davidson, G.; Schaugaard, B. T.; Anderson, M.; Johnson, A. W. (International Journal of Exercise Science Conference Proceedings, 2025)
Female gymnasts have a high rate of injury due to the repetitive nature and high forces of the sport. Repetition of movements is necessary to improve confidence and perfect execution. However, such repetition may also lead to overloading the Achilles tendon (AT) and increases potential of tendinopathy. Gymnasts generally perform the same skills repetitively using a preferred leg, e.g. always jumping off the right leg entering the vault.